Takie buty? Commedia della lingua Tymoteusza Karpowicza - Bogalecki, Piotr (Śląskie Studia Polonistyczne, 2015)
The article constitutes an attempt at an extended analysis of Tymoteusz Karpowicz’s posthumously published poem, Commedia dell’arte, which concentrates on numerous intertextual references operating within it (for example the references to D. Defoe’s and Ch. Baudelaire’s texts, to the figure of a fool, G. Tiepol’s painting or Bolesław Leśmian’s poems). It is the author’s firm belief that these references cannot be treated as mere erudite ornaments but should be acknowledged as the strategies revealing the hidden sense of the text. The latter turn out to lead the reader in the direction which shall be today called postsecular: although the text talks about God who has abandoned the world, and as such may be recognized as a story about secularization, I treat it as “inscribed positively in the destiny of kenosis” (G. Vattimo). Such a reading may be supported by a mimological correspondence between the strategies hindering a reading on the plane of expression and an affirmation of kenosis on the plane of content.